Sustainability analysis for irrigation water management: concepts, methodology, and application to the Aral Sea region - Cai, Ximing; McKinney, Daene C.; Rosegrant, Mark W. (International Food Policy Research Institute, 2001)
Sustainable irrigation water management should simultaneously achieve two objectives: sustaining irrigated agriculture for food security and preserving the associated natural environment. A stable relationship should be maintained between these two objectives now and in the future, while potential conflicts between these objectives should be mitigated through appropriate irrigation practices. Lessons learned from unsustainable water management practices around the world demonstrate the necessity—and growing urgency—of applying sustainability principles to water management in river basins where irrigation is a major factor. This paper presents the operational concepts and analytical framework for sustainability analysis of irrigation water management in irrigation-dominated river basins. These are applied to the Aral Sea region in Central Asia, a region famous for its conflict between sustaining irrigated agriculture and preserving the environment. Maintaining current irrigation practices will lead to worsening environmental and economic consequences. Infrastructure improvements and changes in crop patterns will be necessary to sustain the irrigated agriculture and the associated environment in the region. A penalty tax on salt discharge, as an economic incentive, may help address environmental problems while having only a small effect on irrigation profit.